2001
DOI: 10.1051/0004-6361:20010218
|View full text |Cite
|
Sign up to set email alerts
|

A wide field survey at the Northern Ecliptic Pole

Abstract: Abstract. We present a medium deep survey carried out in the three filters Bj, R and K. The survey covers homogeneously the central square degree around the Northern Ecliptic Pole (NEP) down to a completeness limit (95%) of 24.25, 23.0 and 17.5 mag in Bj, R and K, respectively. While the near infrared data have been presented in the first paper of this series, here we concentrate on the optical data and the results based on the combined BjRK-data. The unique combination of area and depth in our survey allows t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
43
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 45 publications
10
43
1
Order By: Relevance
“…Figure 5 shows a comparison of pointlike star counts. The diamonds represent our star counts, and the squares represent those of Kümmel & Wagner (2000). Our star counts at 16:5 < K s < 17:0 are lower than those of Kümmel & Wagner (2000) because our star counts are classified on the basis of the optical image profiles and some saturated pointlike objects are removed from the catalog.…”
Section: Star-galaxy Separationmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 5 shows a comparison of pointlike star counts. The diamonds represent our star counts, and the squares represent those of Kümmel & Wagner (2000). Our star counts at 16:5 < K s < 17:0 are lower than those of Kümmel & Wagner (2000) because our star counts are classified on the basis of the optical image profiles and some saturated pointlike objects are removed from the catalog.…”
Section: Star-galaxy Separationmentioning
confidence: 99%
“…The bump is also seen in recent results from wide and deep surveys, although the fainter counts of wide-field surveys (e.g., 7.1 deg 2 ; Elston et al 2006) require a correction for completeness, while the brighter counts of deep surveys (e.g., Roche et al 2003;Caputi et al 2005;Förster Schreiber et al 2006) have large errors due to the lower number of galaxies. It was also reported that galaxy populations below the turning point of the K-band count slope tend to have bluer optical-NIR colors (e.g., Gardner et al 1993;Gardner 1995;Djorgovski et al 1995;Saracco et al 1997Saracco et al , 1999Bershady et al 1998;McCracken et al 2000;Huang et al 2001;Kümmel & Wagner 2001). On the other hand, papers describing the J-band galaxy counts published to date number only a few.…”
Section: Introductionmentioning
confidence: 99%
“…We compare our total sample estimate of the amplitude, A ω at 1 deg, of the angular correlation function with a compilation of results from the literature. We include mesurements from: Daddi et al (2000), Kümmel & Wagner (2001), McCracken et al (2000b), Daddi et al (2003) and Roche et al (2003). The continous, dotted and dashed lines show, for reference, the models of PLE from Roche et al (1998), with scaling from local galaxy clustering.…”
Section: Clustering Of Extended Sourcesmentioning
confidence: 99%
“…Each SN site was observed for 2 h in total, divided into ten exposures with 720 s each. To find even very faint objects, we chose to observe with an exceptionally wide filter available at CAHA: the BV Roeser filter (Kümmel & Wagner 2001). In comparison to standard Johnson filters (e.g.…”
Section: Observations and Archival Datamentioning
confidence: 99%
“…Kümmel & Wagner 2001). We adjusted the photometric zero-point SExtractor uses for magnitude computation in an iterative process such that the extracted magnitudes agree to within the < ∼ 0.2 mag scatter with those of the reference stars selected Notes.…”
Section: Data Reductionmentioning
confidence: 99%